Green public procurement and the innovation activities of firms - Vera Zipperer (Deutsches Institut für Wirtschaftsforschung (DIW), 2019)
This paper provides first empirical insights on the relationship between green public procurement (GPP) and firms' innovation activities. Considering that the public sector is a large buyer in the economy, public procurement is able to work as demand-pull factor for new products and thus innovations - given that the procurement is aimed at such objectives. GPP is specifically implemented to contribute to more sustainable production and consumption. Using a novel firm-level dataset, this paper analyses whether GPP is able to trigger innovation activities within firms, and if so, whether these innovations are environmental innovations or not. The results show some support for a demand-pull effect of GPP on the probability of general product innovations but no conclusive evidence is found for environmental innovations.
Keywords: H57; O38; Q55; Q58; 330; Green public procurement; Innovation; Demand-pull; Community innovation survey